Heat Treatments of Metastable β Titanium Alloy Ti-24Nb-4Zr-8Sn Processed by Laser Powder Bed Fusion - Hein, Maxwell; Lopes Dias, Nelson Filipe; Pramanik, Sudipta; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (Materials)

Sprechertypen in der Forschung und in der Exploration für den Dialektatlas Mittleres Westdeutschland - Wallmeier, Nadine; Gehrke, Gero; Reinhardt, Katrin; Sauermilch, Stephanie (Niederdeutsches Wort)

INGRID – Das Informationssystem Graffiti in Deutschland - Niemann, Sven (HipHop im 21. Jahrhundert)

Relationen von Professionswissen und Performanz im Praxissemester Physik. - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2021.)

Ansätze zur Ermittlung von Kompetenzniveaus im Fachdidaktischen Wissen - Zeller, Jannis; Jordans, Melanie; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2021)

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Development of a test method for investigating the leak tightness of hybrid joined battery housing connections - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)
Keywords: Polymers and Plastics; General Chemical Engineering; Biomaterials

Fatigue strength of adhesively butt-bonded hollow cylinders under multiaxial loading with constant and variable amplitudes - Hecht, Matthias; Baumgartner, Jörg; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

Wage Bargaining and Employment Revisited: Separability and Efficiency in Collective Bargaining - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya (Scandinavian Journal of Economics)
We analyse the two-dimensional Nash bargaining solution (NBS) by deploying the standard labour market negotiations model of McDonald and Solow (1981). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems, such that the two solutions together replicate the solution of the two-dimensional problem if the NBS is applied. The axiom of Independence of Irrelevant Alternatives is shown to be crucial for this type of decomposability. This result has significant implications for actual negotiations because it allows for the decomposition of a multi-dimensional bargaining problem into one-dimensional problems---and thus helps to facilitate real-world negotiations.
Keywords: Labour market negotiations; efficient bargains; Nash bargaining solution; sequential bargaining; restricted bargaining games

Increasing the Prediction Quality of Clinching Process Simulation with Extensible Die by Means of Friction Modeling as a Function of the Local Joining Process Parameters - Rossel, Moritz Sebastian; Meschut, Gerson

Existence of Ground States in the Infrared-Critial Spin Boson Model - Hinrichs, Benjamin (Mathematical aspects of quantum fields and related topics)
We review recent results on the existence of ground states for the infrared-critical spin boson model, which describes the interaction of a massless bosonic field with a two-state quantum system. Explicitly, we derive a critical coupling $λ_{\mathsf c}>0$ such that the spin boson model exhibits a ground state for coupling constants $λ$ with $|λ|<λ_{\mathsf c}$. The proof combines a Feynman-Kac-Nelson formula for the spin boson model with external magnetic field, a 1D-Ising model correlation bound and a compactness argument in Fock space. Elaborating on the connection to a long-range 1D-Ising model, we briefly discuss the conjecture that the spin boson model does not have a ground state at large coupling. This note is based on joint work with David Hasler and Oliver Siebert.

Broadband Mach-Zehnder Modulator with Linear Driver in Electronic-Photonic Co-Integrated Platform - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Kerman, Sarp; Scheytt, J. Christoph (Optica Advanced Photonics Congress 2022)
A monolithically integrated electronic-photonic Mach-Zehnder modulator is presented, incorporating electronic linear drivers along photonic components. An electro-optical 3 dB & 6 dB bandwidth of 24 GHz and 34 GHz respectively was measured. The on-chip drivers decrease the V π by a factor of 10.

Zum Einstieg: Master-Arbeit zu ökologischer und sozial gerechter Stadtplanung. Ein fiktives Beispiel - Freymuth, Nina (Wissenschaftsläden in der Sozialen Arbeit. Partizipative Forschung und soziale Innovationen)

„Ich hab als Erstes die angeguckt“ – Muster- und Strukturerkennung mit Eye-Tracking besser verstehen? - Bruns, Julia; Reuter, D. (Beiträge zum Mathematikunterricht 2022)

Effects of Facilitator Professional Development on Teachers’ Learning – An Intervention Study in the Context of Early Mathematics Education - Bruns, Julia; Hagena, M.; Gasteiger, H. (Proceedings of the Twelfth Congress of the European Society for Research in Mathematics Education (CERME12))

Entwicklung und Validierung eines videobasierten Testinstruments zur Erfassung des Noticing mit dem Fokus auf Anerkennungsprozesse im inklusiven Sportunterricht - Bruns, Julia; Langer, W.; Erhorn, J. (German Journal of Exercise and Sport Research)

Development and validation of a video-based test instrument to measure noticing with regard to processes ofrecognition in inclusive physical education - Langer, Wiebke; Bruns, Julia; Erhorn, Jan (German Journal of Exercise and Sport Research)
The construct of noticing is considered to be of crucial importance for professional action of (prospective) physical education (PE) teachers in the context of (inclusive) PE. In order to implement the demands of inclusive PE teaching, noticingwith regard to processes of recognition proves to be particularly significant. Due to the relevance of physicality, the design of recognition relationships that encourage pupils' development results in specific requirements for the selective attention and the theory-based interpretation of processes of recognition and disregard in complex teaching situations. This facet of competence has hardly been studied so far, partly due to the lack of instruments for standardised assessment of this construct. In the context of this paper, the development and validation of a standardised, video vignette-based test instrument for the measurement of noticingwith regard to processes of recognition of prospective PE teachers is presented. The validation focuses on the content of the test and the internal structure of the instrument as well as on correlations with related constructs in terms of content. The results from three consecutive validation studies provide indications of the reliability and validity of the test score interpretation of the instrument ViProQiS_A. The findings so far indicate that the standardised measurement of noticingwith regard to processes of recognitionin inclusive PE could be realized on the basis of the test instrument developed here.
Keywords: Physical education teacher education; Competence modelling and; measurement; Inclusive physical education; Video-based items; Noticing

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Muster- und Strukturerkennungsprozesse bei potenziell mathematisch begabten Grundschulkindern untersuchen – Das Potenzial von Eye-Tracking und retrospektivem Interview im Vergleich - Reuter, Dinah; Bruns, Julia (Eye-Tracking in der Mathematik- und Naturwissenschaftsdidaktik)

inklud-e: Sensibilität für Inklusion durch Fallarbeit entwickeln - Professionalisierung angehender Grundschullehrkräfte in digitalen Lehr-/Lernformaten - Herding, Jana; Büker, P.; Glawe, K.; Menke, I. (Reflexion und Reflexivität im Kontext Grundschule. Perspektiven für Forschung, Lehrer:innenbildung und Praxis. Jahrbuch Grundschulforschung)